2009
DOI: 10.1523/jneurosci.5060-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Truncated TrkB.T1 Receptor Regulates Neuronal Complexity and TrkB Kinase Receptor FunctionIn Vivo

Abstract: Pathological or in vitro overexpression of the truncated TrkB (TrkB.T1) receptor inhibits signaling through the full-length TrkB (Trk-B.FL) tyrosine kinase receptor. However, to date, the role of endogenous TrkB.T1 is still unknown. By studying mice lacking the truncated TrkB.T1 isoform but retaining normal spatiotemporal expression of TrkB.FL, we have analyzed TrkB.T1-specific physiological functions and its effect on endogenous TrkB kinase signaling in vivo. We found that TrkB.T1-deficient mice develop norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
128
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 53 publications
4
128
0
Order By: Relevance
“…The immunomarker, brain-derived neurotrophic factor was adopted for the present study due to its functional significance in the control of neurogenesis, dendritic growth and synaptic plasticity (Carter et al, 2002;Carim-Todd et al, 2009). The result of the present study revealed a wide-spread localisation of brain-derived neurotrophic factor protein in the olfactory bulb of the African grasscutter at different postnatal periods, and the protein was confined to some specific neurones.…”
Section: Discussionmentioning
confidence: 67%
“…The immunomarker, brain-derived neurotrophic factor was adopted for the present study due to its functional significance in the control of neurogenesis, dendritic growth and synaptic plasticity (Carter et al, 2002;Carim-Todd et al, 2009). The result of the present study revealed a wide-spread localisation of brain-derived neurotrophic factor protein in the olfactory bulb of the African grasscutter at different postnatal periods, and the protein was confined to some specific neurones.…”
Section: Discussionmentioning
confidence: 67%
“…We found that BDNF induced a sustained increase in TrkB-T1 receptors are predominantly expressed in rat astrocytes (33), while the expression of TrkB-FL receptors is up-regulated after brain injury (55). Although the physiological significance of truncated TrkB receptors is still unknown (38,56), several studies support the importance of TrkB-T1 receptors in the CNS. In cultured rat astrocytes, TrkB-T1 receptors mediate the BDNF-induced elevation of [Ca 2ϩ ]i (33) and are involved in their morphological changes (45).…”
Section: Discussionmentioning
confidence: 86%
“…In cultured rat astrocytes, TrkB-T1 receptors mediate the BDNF-induced elevation of [Ca 2ϩ ]i (33) and are involved in their morphological changes (45). Carim-Todd et al (56) have recently reported that TrkB-T1-deficient mice develop normally but have increased anxiety-like behavior, accompanied by morphological abnormalities in the dendrites of neurons in the basolateral amygdala. In the present study, we demonstrated that TrkB-T1 receptors were highly expressed in rodent microglial cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mice that are deficient in TrkB, the Bdnf receptor, show morphological alterations in the amygdala and increased anxiety-like behavior. 30 Additionally, Bdnf was shown to be critical for fluoxetine induced fear extinction. 31 Finally, in human carriers of the Bdnf Val66Met polymorphism, which is associated with depression and anxiety, show reductions in amygdala volume.…”
Section: Discussionmentioning
confidence: 99%